Adherence to 24-hour movement guidelines among Portuguese preschool children: the prestyle study - Vale, Susana; Mota, Jorge (Journal of sports sciences, 2020)
The 24-Hour Movement Guidelines (24 hMG) provide specific recommendations, including physical activity (PA), screen-time and sleep-duration, which preschoolers should achieve for a healthy day (24 h). The aim of the current study was to analyse preschooler's adherence with the 24-Hour Movement Guidelines. The sample comprised 739 preschool children. PA was accelerometer-derived. Screen time and sleep duration were parent-reported through questionnaires. Preschoolers were classified as meeting/not meeting in each guideline and as well as for the overall 24hMG. According to the 24hMG, we found high percentages of preschoolers that met sleep guidelines (80.6%), only around 1/3 of preschool children met PA (28.6%) and a lower proportion met screen-time guidelines (20.3%). We found that 31.7% of the children met at least 2 of the recommendations and that more than half only one (52.8%). Overall, 4.5% of preschool children complied with the 24hMG and 11.1% of the children did not comply with any of the three recommendations. Few preschoolers met PA and screen-time recommendations, which deeply impacts the preschooler's adherence to the 24hMG. Future work should focus on finding solutions for promoting better adherence and mainly identifying ways to reduce screen time and increase PA at these ages.